Pernikahan Beda Agama dalam Perspektif Hukum Keluarga Islam - Eti Karini; A. Kumedi Ja’far (CV. Creative Tugu Pena, 2024)
Marriage is an important foundation in family life, especially in Muslim society, but interfaith marriage is a complicated and controversial issue. Although the Indonesian Ulema Council (MUI) fatwa prohibits interfaith marriage, this phenomenon continues to increase, causing social problems and pressure from the environment. Therefore, it is important to understand the perspective of Islamic family law to find a balanced solution between personal beliefs and harmonious life in society. The objectives of this study are: (1) To determine the views of Islamic family law on interfaith marriage; (2) To determine the application of Islamic family law in cases of interfaith marriage in Indonesian religious courts; (3) To determine the impact of interfaith marriage on family relationships. The research method used in this study is library research using a descriptive qualitative approach. While the data collection technique used is documentation. The data sources used are various studies. The technical analysis of descriptive data and analysis of theoretical content that discusses the topic of use is the Appendorff analysis. The results of this study are: (1) The view of Islamic law on interfaith marriage is prohibited or forbidden, this is emphasized in the Compilation of Islamic Law in Indonesia and supported by the MUI fatwa; (2) The application of Islamic family law in cases of interfaith marriage in Indonesian religious courts is carried out by considering the provisions contained in the Compilation of Islamic Law (KHI) and fatwas issued by the MUI, (3) The impact of interfaith marriage on family relationships has a significant negative impact on family relationships. These impacts include psychological pressure, mental conflict, and tension in relationships, which are difficult to overcome if religious differences are not resolved.